Strategi Penanganan Anak Putus Sekolah di Provinsi Lampung (Studi Pada Dinas Pendidikan dan Kebudayaan Provinsi Lampung dalam Menangani Anak Putus SMA Tahun 2021) - Zanu Venti Ryana; Meiliyana Meiliyana; Anisa Utami (Jurnal Administrativa, 2023)
School dropouts have been a problem in the world of education for a long time caused by various factors, one of which is economic factors. The Education and Culture Office of Lampung Province as one of the Regional Apparatus Organizations (OPD) has the authority and responsibility in solving the problems of school dropouts, by issuing the best strategies so that these problems get the right treatment. The purpose of this study is to find out the Strategy of the Lampung Province Education and Culture Office in Handling High School Dropouts in 2021 in Lampung Province. Data collection techniques were carried out through interviews, observations and documentation by looking at four indicators of the types of strategies, namely Organizational Strategy, Program Strategy, Resource Support Strategy, and Institutional Strategy. Based on the results of the study, it was found that the Covid-19 pandemic affected the rate of dropouts in Lampung Province. And the conclusion of the research shows that: 1). The Organization's strategy is based on the vision and mission with the output in the form of a program for improving and equalizing the quality of high school education, with derivative programs in the form of BOSDA and PIP, 2). Program Strategy with the implementation of the BOSDA and PIP Programs has a positive impact on students in continuing their education, 3). Resource Support Strategy by providing a budget for education costs, 4). Institutional Strategy carries out responsibilities and authorities in accordance with SOPs or applicable rules. There are 3 inhibiting factors, namely the refocusing of the budget, the lack of integration of the Population Identification Number (NIK) with the Basic Education Data (Dapodik), the low contribution of the business world and industry in supporting education development.